Effect of erythrophagocytosis-induced ferroptosis during angiogenesis in atherosclerotic plaques - Pauline Puylaert; Lynn Roth; Melissa Van Praet; Isabel Pintelon; Catalina Dumitrascu; Alexander van Nuijs; Greta Klejborowska; Pieter-Jan Guns; Tom Vanden Berghe; Koen Augustyns; Guido R. Y. De Meyer; Wim Martinet (Angiogenesis, 2023)
Intraplaque (IP) angiogenesis is a key feature of advanced atherosclerotic plaques. Because IP vessels are fragile and leaky, erythrocytes are released and phagocytosed by macrophages (erythrophagocytosis), which leads to high intracellular iron content, lipid peroxidation and cell death. In vitro experiments showed that erythrophagocytosis by macrophages induced non-canonical ferroptosis, an emerging type of regulated necrosis that may contribute to plaque destabilization. Erythrophagocytosis-induced ferroptosis was accompanied by increased expression of heme-oxygenase 1 and ferritin, and could be blocked by co-treatment with third generation ferroptosis inhibitor UAMC-3203. Both heme-oxygenase 1 and ferritin were also expressed in erythrocyte-rich regions of carotid plaques from ApoE −/− Fbn1 C1039G+/− mice, a model of advanced atherosclerosis with IP angiogenesis. The effect of UAMC-3203 (12.35 mg/kg/day) on atherosclerosis was evaluated in ApoE −/− Fbn1 C1039G+/− mice fed a western-type diet (WD) for 12 weeks (n = 13 mice/group) or 20 weeks (n = 16–21 mice/group) to distinguish between plaques without and with established IP angiogenesis, respectively. A significant decrease in carotid plaque thickness was observed after 20 weeks WD (87 ± 19 μm vs. 166 ± 20 μm, p = 0.006), particularly in plaques with confirmed IP angiogenesis or hemorrhage (108 ± 35 μm vs. 322 ± 40 μm, p = 0.004). This effect was accompanied by decreased IP heme-oxygenase 1 and ferritin expression. UAMC-3203 did not affect carotid plaques after 12 weeks WD or plaques in the aorta, which typically do not develop IP angiogenesis. Altogether, erythrophagocytosis-induced ferroptosis during IP angiogenesis leads to larger atherosclerotic plaques, an effect that can be prevented by ferroptosis inhibitor UAMC-3203.

Comparative study of the organisation and phenotypes of bladder interstitial cells in human, mouse and rat - Thomas Gevaert; Jochen Neuhaus; Els Vanstreels; Dirk Daelemans; Wouter Everaerts; Frank Van Der Aa; Jean-Pierre Timmermans; Tania Roskams; Clara Steiner; Isabel Pintelon; Dirk De Ridder (Cell and Tissue Research, 2017)

In situ proximity of CX3CR1-positive mononuclear phagocytes and VIP-ergic nerve fibers suggests VIP-ergic immunomodulation in the mouse ileum - Roeland Buckinx; Katrien Alpaerts; Isabel Pintelon; Nathalie Cools; Luc Van Nassauw; Dirk Adriaensen; Jean-Pierre Timmermans (Cell and Tissue Research, 2017)

GABAergic signaling in the pulmonary neuroepithelial body microenvironment: functional imaging in GAD67-GFP mice - Kathy Schnorbusch; Robrecht Lembrechts; Isabel Pintelon; Jean-Pierre Timmermans; Inge Brouns; Dirk Adriaensen (Histochemistry and Cell Biology, 2013)

Effects of aging and exercise training on the histological and mechanical properties of articular structures in knee joints of male rat - Hideki Moriyama; Naohiko Kanemura; Inge Brouns; Isabel Pintelon; Dirk Adriaensen; Jean-Pierre Timmermans; Junya Ozawa; Nobuhiro Kito; Toshiaki Gomi; Masataka Deie (Biogerontology, 2012)

Expression of mechanogated two-pore domain potassium channels in mouse lungs: special reference to mechanosensory airway receptors - Robrecht Lembrechts; Isabel Pintelon; Kathy Schnorbusch; Jean-Pierre Timmermans; Dirk Adriaensen; Inge Brouns (Histochemistry and Cell Biology, 2011)

Neurochemical pattern of the complex innervation of neuroepithelial bodies in mouse lungs - Inge Brouns; Fusun Oztay; Isabel Pintelon; Ian Proost; Robrecht Lembrechts; Jean-Pierre Timmermans; Dirk Adriaensen (Histochemistry and Cell Biology, 2009)

Pulmonary expression of voltage-gated calcium channels: special reference to sensory airway receptors - Ian Proost; Inge Brouns; Isabel Pintelon; Jean-Pierre Timmermans; Dirk Adriaensen (Histochemistry and Cell Biology, 2007)

Selective visualisation of sensory receptors in the smooth muscle layer of ex-vivo airway whole-mounts by styryl pyridinium dyes - Ian De Proost; Isabel Pintelon; Inge Brouns; Jean-Pierre Timmermans; Dirk Adriaensen (Cell and Tissue Research, 2007)

Neurochemical characterisation of sensory receptors in airway smooth muscle: comparison with pulmonary neuroepithelial bodies - Inge Brouns; Isabel Pintelon; Ian Proost; Roel Alewaters; Jean-Pierre Timmermans; Dirk Adriaensen (Histochemistry and Cell Biology, 2006)

Vesicular glutamate transporter2 is expressed in different nerve fibre populations that selectively contact pulmonary neuroepithelial bodies - Inge Brouns; Isabel Pintelon; Jeroen Van Genechten; Ian De Proost; Jean-Pierre Timmermans; Dirk Adriaensen (Histochemistry and Cell Biology, 2004)